Pengaruh Urbanisasi, Modal Manusia, dan Pengangguran terhadap Kemiskinan Perkotaan di Enam Kota Provinsi Jawa Tengah Tahun 2015-2021 - Jihan Sabilillah; Mulyo Hendarto Robertus (Universitas Diponegoro, 2024)
Urban poverty in six cities in Central Java Province is an interesting issue to analyze in relation to the factors that influence it. This study analyzes the issue of urban poverty because regional economic development is partly determined by how cities can grow. The objective of this research is to analyze the effect of urbanization, human capital, and unemployment on urban poverty in six cities in Central Java Province from 2015 to 2021. This study uses quantitative data sourced from publications by the Badan Pusat Statistik of Central Java Province. The method used is multiple linear regression with panel data, where the dependent variable is the percentage of the poor population, while the independent variables include urbanization (in-migration), human capital (HDI), and unemployment in the cities of Magelang, Surakarta, Tegal, Semarang, Pekalongan, and Salatiga from 2015 to 2021. The results of the study show that urbanization has a positive and significant effect on poverty, human capital has a negative and significant effect on poverty, and unemployment has a positive and significant effect on poverty.